PENGARUH PEMBELAJARAN LISTENING MELALUI YOUTUBE UNTUK MENINGKATKAN KEMAMPUAN LISTENING TARUNA - Fatmawati Fatmawati; Laila Rochmawati; Meita Maharani Sukma; Rinto Astutik (Approach : Jurnal Teknologi Penerbangan, 2019)
You Tube about an emergency situation is believed to be the bearer of the technological revolution in relation to pedagogy, which can provide more comfortable access to language input materials, such as hearing, visuals, and other authentic types of resources to promote progress in all four language learning skills namely listening, speaking , reading and writing. Among these skills, for flight communication cadets and air traffic, listening comprehension provides the opening key to access to language mastery. This study examines and analyzes the effects of YouTube video clips on emergency situations as teaching material for flight communication cadets and Surabaya air traffic policing on their hearing comprehension performance. In more detail, this compares the effect of using various amounts of YouTube clips in three experimental groups with those found in a control group where no clips were used. Certain numbers of YouTube video clips about emergency situations - two, four, or six - used for each group represent an attempt to find out how many results were optimized. The subject of his research, 75 cadets of aviation communication and air traffic in Surabaya Polytechnic participated in a fourteen-week experimental study. Pre and post tests and background surveys are used for the control group (0-video) and experimental (2-video, 4-video, and 6 video clips).